Structural characterization and Rietveld refinement of potassium nickel hexacyanoferrate KNi[Fe(CN)6] nano composites prepared via Co-precipitation method. (2022) - Narayan, Bhism; Rohilla, Sunil; Patwa, Rahul
Abstract: Prussian Blue and its analogues based Nickel Hexacyanoferrate shows a number of application. Here we mixed potassium ion with nickel hexacyanoferrate and prepared Potassium Nickel Hexacyanoferrate to improve its applications. Prepared nano composites were synthesized by using Co-precipitation method. The structural analysis of prepared nano composite was studied by using X-Ray diffraction technique. Data comes out from X-Ray diffraction was refined through Rietveld method by using full prof suit software. Structure related other parameters were also studied here. The KNi[Fe(CN)6 ] shows FCC cubic structure with space group F m-3 m (2 2 5). Some measurement like Inter atomic distance, bond angle, half width, and lattice parameters were study in detail. The wyckoff position of different atom with site and S.O.F have been calculated. Infrared spectra of potassium Nickel hexacyanoferrate also are study here. Some application related to it in radioactive particle absorption from nuclear wastage and as an electrode in batteries. More applications of Potassium Nickel Hexacyanoferrate come into light on further research in this field.